Promoting Preservice Teachers' Attitudes toward Socioscientific Issues - Sundus Yerdelen; Mustafa Cansız; Nurcan Cansız; Hakan Akcay (Seyit Ahmet Kıray, 2018)
In this study, we aimed to improve preservice teachers' attitudes toward socioscientific issues through socioscientific issue course. Moreover, we investigated whether this course influences preservice teachers studying in a science education and non-science education in a similar way. For this purpose, a semester-long socioscientific issues course was designed and implemented. Data were collected from a science education group (preservice science teachers) and a non-science education group (preservice social-science teachers). In order to evaluate participants' attitudes towards socioscientific issues, Attitudes towards Socioscientific Issues Scale was utilized before and after the course. This scale evaluates attitudes under three themes: liking of socioscientific issues, interest and usefulness of socioscientific issues, and anxiety towards socioscientific issues. The result revealed that socioscientific issues course provided similar gains for both preservice science teachers and preservice social-science teachers on interest and usefulness of socioscientific issues, liking of socioscientific issues, and anxiety towards socioscientific issues. That is both groups derived a similar benefit from the socioscientific issues course. Specifically, socioscientific issues course contributed to preservice teachers' interest and usefulness of socioscientific issues, and liking of socioscientific issues positively. On the other hand, their anxiety scores did not change significantly after the course. These findings imply that, regardless of majors, socioscientific issues course has potential to favor preservice teachers' attitudes toward socioscientific issues.